2015
DOI: 10.1111/papt.12077
|View full text |Cite
|
Sign up to set email alerts
|

Sexual problems and post‐traumatic stress disorder following sexual trauma: A meta‐analytic review

Abstract: The measurement of sexual problems is overlooked in psychological treatment RCTs for sexual trauma. Current treatments for post-traumatic stress disorder (PTSD) from sexual trauma do not appear to be addressing sexual problems. Integrated treatments for comorbid sexual problems and PTSD treatment may be warranted. It is imperative that in future, RCTs that examine people with PTSD from sexual trauma use outcomes of sexual problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…It is possible that existing couples’ therapies used in SM/Vs (e.g., Conjoint Behavior Couples’ Therapy [Monson & Fredman, ]; Emotion Focused Therapy [Johnson & Greenberg, ]) could be augmented to explore and treat sexual issues, particularly since individual PTSD treatments do not improve sexual functioning (see review, O'Driscoll & Flanagan, ). Interventions that focus on processing the sexual trauma, helping the traumatized individual see themselves as a survivor rather than as a victim, enhancing the survivor's perception that sexual experiences are safe and consensual, and fostering the belief that the healing process is a joint effort between the survivor and their romantic partner may be particularly beneficial in addressing sexual trauma, relationship satisfaction, sexual dysfunction, and sexual dissatisfaction (McCarthy & Farr, ; Meston, Lorenz, & Stephenson, ; Nasim & Nadan, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that existing couples’ therapies used in SM/Vs (e.g., Conjoint Behavior Couples’ Therapy [Monson & Fredman, ]; Emotion Focused Therapy [Johnson & Greenberg, ]) could be augmented to explore and treat sexual issues, particularly since individual PTSD treatments do not improve sexual functioning (see review, O'Driscoll & Flanagan, ). Interventions that focus on processing the sexual trauma, helping the traumatized individual see themselves as a survivor rather than as a victim, enhancing the survivor's perception that sexual experiences are safe and consensual, and fostering the belief that the healing process is a joint effort between the survivor and their romantic partner may be particularly beneficial in addressing sexual trauma, relationship satisfaction, sexual dysfunction, and sexual dissatisfaction (McCarthy & Farr, ; Meston, Lorenz, & Stephenson, ; Nasim & Nadan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have consistently found that PTSD is often associated with sexual dysfunction, and this is particularly true for PTSD secondary to sexual trauma (Yehuda, Lehrner, & Rosenbaum, ). However, little research has focused specifically on the relationship between PTSD and difficulties with sexuality among female sexual trauma survivors (O'Driscoll & Flanagan, ).…”
Section: The Effects Of Sexual Traumamentioning
confidence: 99%
“…Despite strong support for trauma‐focused, evidence‐based treatments (EBTs), these treatments neither specifically nor intentionally address the various sexual concerns that may follow a sexual assault, such as changes to intimate relationships, sexual expression, and sexual self‐concept. A recent meta‐analysis of the few studies that examine their effectiveness found little evidence that treatment for PTSD had an effect on sexual problems among survivors of sexual assault (O'Driscoll & Flanagan, ). In addition to not receiving help for concerns related to sexuality, failing to address them directly in therapy may reinforce to the client that these topics are either unimportant or unsafe to discuss, even with her therapist.…”
Section: The Effects Of Sexual Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…SV history is associated with fear of sex (Van Berlo & Ensink, 2000) and elevated sexrelated distress (i.e., distress associated with sexuality or sexual activity) has been reported among women with histories of SV (Siegel et al, 1990;Stephenson, Hughan, & Meston, 2012;Ullman & Siegel, 1993). Such links between SV history with fear and with sex-related distress are likely due to the fact that sexual activity serves as a trigger or reminder of the traumatic event (O'Driscoll & Flanagan, 2016). Accordingly, sex-related distress worsens with assaults that included penetration (i.e., those that are more severe; Lemieux & Byers, 2008;Siegel et al, 1990) and may persist even when the sexual assault occurred one or more years ago (Siegel et al, 1990;Van Berlo & Ensink, 2000).…”
mentioning
confidence: 99%